ANALISIS PENGENDALIAN INTERNAL ATAS PERSEDIAAN SPARE PART PADA CV. SURYA PRIMA BANJARBARU - Pipit Angelia Widiarti; Rizky Mauladi, Siti Fatimah (CV. ADIBA AISHA AMIRA, 2023)
The method used is research that is used, namely descriptive qualitative research, descriptive research that requires original data from the company, namely internal control over spare parts for 2 (two) wheeled vehicles on CV. Surya Prima Banjarbaru which has been carried out so far as material for analyzing internal control over spare parts for 2 (two) wheeled vehicles at CV. Surya Prima Banjarbaru which should be carried out for 3 (three) months. The results of this study indicate that so far CV. Surya Prima Banjarbaru has not established a written Part Request and Purchase Procedure as well as a Part Purchase Procedure and Part Storage Procedure at the Dealer because many pivot parts are stored for a long time, the current system application is only used for recording incoming and outgoing parts not connected with transaction authorization activities, already exists segregation of duties but there is still work that can be done in several positions, there is no sufficient specific document, especially recording the inventory of Dealer parts, so far the recording of expenses has only been carried out based on incoming and outgoing goods with the application system. CV.Surya Prima Banjarbaru should correct this discrepancy not only in terms of application and transaction recording procedures for the progress of the company as well as recording of financial reports in accordance with Generally Accepted Accounting Principles (PABU) and the realization of a good supply of parts in CV. Surya Prima Banjarbaru and the creation of good internal control, especially with the existence of a financial section that plays an important role in the internal control system for part inventory that is connected to the application to all authorized parties because it will make work effective and fast and prevent falsification of documents and fraud that can be done by worker